Translating molecular advances in Down syndrome and Fragile X syndrome into therapies - Faundez, V; De Toma, I; Bardoni, B; Bartesaghi, R; Nizetic, D; de la Torre, R; Kadosh, R; Herault, Y; Dierssen, M; Potier, M-C (Elsevier, 2018)
Ongoing treatments for genetic developmental disorders of the central nervous system are mostly symptomatic and do not correct the genetic cause. Recent identification of common mechanisms between diseases has suggested that new therapeutic targets could be applied across intellectual disabilities with potential disease-modifying properties. The European Down syndrome and other genetic developmental disorders (DSG2D) network joined basic and clinical scientists to foster this research and carry out clinical trials. Here we discuss common mechanisms between several intellectual disabilities from genetic origin including Down's and Fragile X syndromes: i) how to model these complex diseases using neuronal cells and brain organoids derived from induced pluripotent stem cells; ii) how to integrate genomic, proteomic and interactome data to help defining common mechanisms and boundaries between diseases; iii) how to target common pathways for designing clinical trials and assessing their efficacy; iv) how to bring new neuro-therapies, such as noninvasive brain stimulations and cognitive training to clinical research. The basic and translational research efforts of the last years have utterly transformed our understanding of the molecular pathology of these diseases but much is left to be done to bring them to newborn babies and children to improve their quality of life.